A high performance ultra-white glass and preparation method thereof

By introducing antibacterial agents such as Ag2SO4, Ag3PO4 and CuSO4 into ultra-white glass, and combining Na2O, MgO and other additives, the problem of both antibacterial properties and transmittance of ultra-white glass is solved, and the preparation of high-performance ultra-white glass is realized. It has excellent antibacterial effect and high visible light transmittance.

CN118290026BActive Publication Date: 2024-12-17QINHUANGDAO AOHUA GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410406888.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-07
Publication Date
2024-12-17
Estimated Expiration
2044-04-07

AI Technical Summary

Technical Problem

Ultra-white glass is difficult to have excellent antibacterial properties and high visible light transmittance. In the prior art, antibacterial agents such as silver nitrate can easily cause yellowing of the glass and reduce the transmittance.

Method used

Ag2SO4, Ag3PO4 and CuSO4 are used as antibacterial agents, and a stable aluminum-oxygen complex structure and Cu2+ and Ag+ are formed through additives such as Na2O, MgO, Al2O3, B2O3, Ca(H2PO4)2, and a stable aluminum-oxygen complex structure and Cu2+ and Ag+ are dispersed in the molten state. Avoid micelles, improve transmittance and antibacterial effects.

Benefits of technology

The ultra-white glass produced has a visible light transmittance of more than 95%, and has excellent antibacterial properties against E. coli and Staphylococcus aureus. The visible light transmittance of long-term outdoor use is still as high as 93%, with significant antibacterial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004777738730000061
    Figure BDA0004777738730000061
  • Figure BDA0004777738730000062
    Figure BDA0004777738730000062
Patent Text Reader

Abstract

The present application specifically discloses a high-performance ultra-white glass and a preparation method thereof. The high-performance ultra-white glass is composed of the following raw materials in weight percentage: SiO2 71.6-72.2%, Na2O 10.1-11.7%, MgO 7.2-8.2%, Al2O3 5.4-8.8%, Ag2SO4 0.001-0.005%, Ag3PO4 0.01-0.03%, CuSO4 0.025-0.05%, B2O3 0.2-0.3%, Ca(H2PO4)2 1.4-2.6%, and Fe2O3 0.008-0.01%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inorganic glass production, and more specifically, to a high-performance ultra-white glass and a preparation method thereof. Background Art

[0002] Ultra-white glass is an ultra-transparent low-iron glass with a light transmittance of more than 91.5%, which is a high-end glass product. Ultra-white glass is currently commonly used in the photovoltaic field, high-end buildings, and ornamental fish tanks. In particular, the photovoltaic field has high requirements for the light transmittance of ultra-white glass. According to relevant research, the light transmittance of ultra-white glass is an important factor affecting the photoelectric conversion efficiency of photovoltaic modules. The higher the light transmittance, the higher the photoelectric conversion efficiency of solar cells. When the photoelectric conversion efficiency of solar cells increases by one percentage point, its power generation cost is reduced by 7%, which has broad development prospects.

[0003] In the related art, the patent with publication number CN116715436A discloses a kind of ultra-white glass for solar energy and its preparation method, and its specific formula (by weight) is: 72-85 parts of silicon dioxide, 5-9 parts of aluminum oxide, 6-11 parts of sodium oxide, 0.6-1.4 parts of barium phosphate, 0.2-0.9 parts of barium metaphosphate, 0.5-1.1 parts of lithium tantalate and 0.4-0.9 parts of composite clarifier; the ultra-white glass obtained has a visible light transmittance of up to 95.4%. Although the visible light transmittance of the obtained ultra-white glass is high, the ultra-white glass cannot be used outdoors for a long time. Under the erosion of rain, bacteria and high temperature, the ultra-white glass is prone to mold problems, and the ultra-white glass surface is sticky and has color spots, which affects the visible light transmittance of the ultra-white glass and leads to a decrease in the long-term service life of the ultra-white glass.

[0004] The patent with publication number CN116947314A discloses an ultra-white antibacterial glass and its preparation method, which uses a silver antibacterial agent, more specifically, silver nitrate. Although the addition of silver nitrate can make ultra-white glass have certain antibacterial properties, due to the active chemical properties of silver, it is easy to cluster in the glass and turn yellow, resulting in a decrease in the visible light transmittance of ultra-white glass.

[0005] Based on the above situation, the visible light transmittance and antibacterial performance of ultra-white glass cannot be taken into account at the same time. The industry urgently needs to develop an ultra-white glass that has both excellent antibacterial effect and high visible light transmittance. Summary of the invention

[0006] In order to solve the problem that ultra-white glass is difficult to have both excellent antibacterial properties and high visible light transmittance, the present application provides a high-performance ultra-white glass and a preparation method thereof.

[0007] In the first aspect, the present application provides a high-performance ultra-clear glass, which adopts the following technical solution:

[0008] A high-performance ultra-white glass, composed of the following raw materials in percentage by weight:

[0009] SiO 2 71.6~72.2%、Na 2 O 10.1~11.7%, MgO 7.2~8.2%, Al 2 O 3 5.4~8.8%、Ag 2 SO 4 0.001~0.005%、Ag 3 PO 4 0.01~0.03%、CuSO 4 0.025~0.05%、B 2 O 3 0.2~0.3%、Ca(H 2 PO 4 ) 2 1.4~2.6%,Fe 2 O 3 0.008~0.01%.

[0010] By adopting the above technical solution, the present invention introduces Ag into the silicate glass matrix. 2 SO 4 、Ag 3 PO 4 and CuSO 4 As an antibacterial agent, it is supplemented with Na 2 O, MgO, Al 2 O 3 , B 2 O 3 , Ca(H 2 PO 4 ) 2 Additives such as chlorinated polyols make the glass have excellent antibacterial properties, and at the same time the visible light transmittance of the glass is improved. The principle is as follows:

[0011] In the molten state, Ag 2 SO 4 and Ag 3 PO 4 With Al 2 O 3 The aluminum oxide complex anion [AlO 4 ] - and Ag + , Ag + With [AlO 4 ] - Form a stable structural formula; at the same time, B 2 O 3As a stabilizer, with Al 2 O 3 The combination makes Ag + exists in the form of Ag, but is not reduced to Ag. Within this doping range, Ag + It can be well dispersed in the silicate glass matrix, and is not prone to problems such as micelles and coloration. CuSO 4 Cu 2+ It is light blue, which can complement the turquoise color of iron ions and achieve physical decolorization;

[0012] CuSO 4 Release SO under low and medium temperature conditions 3 Gas, Ag 2 SO 4 At high temperatures, SO is released 3 gas; on the one hand, due to CuSO 4 、Ag 2 SO 4 The decomposition temperature is different, which can reduce the viscosity of the glass melt during both low and medium temperature and high temperature full melting processes, overcoming the Al 2 O 3 The defect of increased melt viscosity caused by the introduction of Cu promotes the fusion of bubbles, and tiny bubbles can be removed during the entire melting process, thereby improving the optical properties of the glass. 2+ 、Ag + There is a synergistic antibacterial effect, which can be achieved at a lower Cu 2+ 、Ag + The addition amount can achieve a good antibacterial effect, and the antibacterial performance is excellent without affecting the light performance of the vitreous body; at the same time, with the discharge of bubbles, Cu 2+ 、Ag + Migrate to the vitreous surface, thus playing a highly effective antibacterial role; furthermore, the SO 3 The gas can maintain the oxidation state of the glass during melting or reheating, preventing the precipitation of silver colloid or silver particles;

[0013] Na 2 O acts as an oxide outside the glass network, further reducing the melt viscosity of the glass and solving the problem of Al 2 O 3 The problem of increased melt viscosity caused by the introduction of Ca(H 2 PO 4 ) 2 、Ag 3 PO 4Containing high-valent phosphorus, it can produce both PO bonding and Si-O bonding, promote the number of bridging oxygen in the silicon-oxygen tetrahedral glass network, increase the density of bridging oxygen connection, enhance the continuity of light transmission in the visible light wavelength range of the glass, and further improve the transmittance of the glass in the visible light region; MgO can inhibit the crystallization tendency of the melt and overcome the B 2 O 3 The addition results in an increase in the average particle size of the glass, thereby improving the optical properties of the glass;

[0014] Ca 2+ Mg 2+ , Cu 2+ The divalent ions can block the diffusion channel of alkali metal ions, that is, they have a blocking effect on the diffusion of alkali metals, reduce the movement of ions, and inhibit the occurrence of mold;

[0015] In summary, the visible light transmittance of the ultra-white glass produced in the present application is as high as over 95%, and it has excellent antibacterial performance against Escherichia coli and Staphylococcus aureus, with the colony count being less than 300 μg / mL; after long-term outdoor environment simulation, the visible light transmittance of the ultra-white glass can still reach over 93%, and it has good antibacterial effect against Escherichia coli and Staphylococcus aureus, with the colony count being less than 300 μg / mL.

[0016] Furthermore, the Ag in the high performance ultra-white glass 2 SO 4 The weight percentage is 0.0025~0.003%, Ag 3 PO 4 The weight percentage is 0.02-0.025%, CuSO 4 The weight percentage is 0.03-0.04%.

[0017] Furthermore, the Ag in the high performance ultra-white glass 2 SO 4 The weight percentage is 0.0025%, Ag 3 PO 4 The weight percentage is 0.025%, CuSO 4 The weight percentage is 0.04%.

[0018] By adopting the above technical solution, the antibacterial agent Ag is adjusted 2 SO 4 、Ag 3 PO 4 and CuSO 4 The weight ratio can enable the antibacterial agent to maintain a good antibacterial effect while ensuring a high visible light transmittance of the vitreous body.

[0019] Furthermore, the Al in the high performance ultra-white glass 2 O 3 The weight percentage is 6.5-7.0%, B 2 O 3 The weight percentage is 0.24-0.26%.

[0020] Furthermore, the Al in the high performance ultra-white glass 2 O 3 The weight percentage is 7.0%, B 2 O 3 The weight percentage is 0.25%.

[0021] By adopting the above technical solution, adjust Al 2 O 3 , B 2 O 3 The weight percentage can effectively stabilize Ag + , reducing the possibility of glass coloring, and avoiding the problem of excessive melt viscosity leading to a decrease in visible light transmittance.

[0022] Furthermore, the Na 2 The weight percentage of O is 10.4-10.6%, Ca(H 2 PO 4 ) 2 The weight percentage of is 2.0-2.6%, and the weight percentage of MgO is 7.5-8.0%.

[0023] Furthermore, the Na 2 The weight percentage of O is 10.5%, Ca(H 2 PO 4 ) 2 The weight percentage of Ag is 2.5%, and the weight percentage of MgO is 7.8%.

[0024] By adopting the above technical solution, adjust Na 2 O and Ca(H 2 PO 4 ) 2 The content of the melt maintains a moderate viscosity without affecting the stability of the melt, the melt is not easy to mold, and does not affect the Cu 2+ 、Ag + of release.

[0025] In a second aspect, the present application provides a method for preparing high-performance ultra-white glass, using the following technical solution;

[0026] A method for preparing high-performance ultra-white glass comprises the following steps:

[0027] The raw materials are weighed according to weight percentage, mixed, ground, melted at high temperature, cooled and formed, and annealed to obtain high-performance ultra-white glass. DETAILED DESCRIPTION

[0028] Example

[0029] Example 1

[0030] A high-performance ultra-white glass, comprising the following raw materials in percentage by weight:

[0031] SiO 2 71.8725%、Na 2 O 10.5%, MgO 7.8%, Al 2 O 3 7.0%、Ag 2 SO 4 0.0025%, Ag 3 PO 4 0.025%, CuSO 4 0.04%, B 2 O 3 0.25%, Ca(H 2 PO 4 ) 2 2.5%, Fe 2 O 3 0.01%;

[0032] Prepare according to the following steps:

[0033] Weigh the corresponding weight percentage of SiO 2 、Na 2 O, MgO, Al 2 O 3 、Ag 2 SO 4 、Ag 3 PO 4 ,CuSO 4 , B 2 O 3 , Ca(H 2 PO 4 ) 2 , Fe 2 O 3 The powder raw materials are preliminarily mixed, put into a zirconia crucible, heated to 500-650°C at a rate of 5°C / min, kept warm for 2-3h, then heated to 900-1080°C at a rate of 3°C / min, kept warm for 0.3-0.5h, then heated to 1490-1630°C at a rate of 2°C / min, kept warm for 4-5h, cooled to 1300°C, and then introduced into a graphite mold for molding;

[0034] Since the graphite mold is preheated to 900±50℃ in advance, annealing is carried out at 900±50℃, annealing is kept for 1 to 3 hours, and then cooled to room temperature at a rate of 3℃ / min. High-performance ultra-white glass is obtained after demolding and polishing.

[0035] Example 2

[0036] A high-performance ultra-white glass, comprising the following raw materials in percentage by weight: SiO 2 71.887%、Na 2 O10.5%, MgO 7.8%, Al 2 O 3 7.0%、Ag 2 SO 4 0.003%, Ag 3 PO 4 0.02%, CuSO 4 0.03%, B 2 O 3 0.25%, Ca(H 2 PO 4 ) 2 2.5%, Fe 2 O 3 0.01%.

[0037] Example 3

[0038] A high-performance ultra-white glass, comprising the following raw materials in percentage by weight: SiO 2 71.6245%、Na 2 O10.1%, MgO 7.2%, Al 2 O 3 8.1%, Ag 2 SO 4 0.0025%, Ag 3 PO 4 0.025%, CuSO 4 0.04%, B 2 O 3 0.3%, Ca(H 2 PO 4 ) 2 2.6%, Fe 2 O 3 0.008%.

[0039] Example 4

[0040] A high-performance ultra-white glass, comprising the following raw materials in percentage by weight: SiO 2 72.2245%、Na 2 O11.7%, MgO 8.2%, Al2 O 3 6.2%, Ag 2 SO 4 0.0025%, Ag 3 PO 4 0.025%, CuSO 4 0.04%, B 2 O 3 0.2%、Ca(H 2 PO 4 ) 2 1.4%, Fe 2 O 3 0.008%.

[0041] Example 5

[0042] A high-performance ultra-white glass, comprising the following raw materials in percentage by weight: SiO 2 71.9625%、Na 2 O10.6%, MgO 8.0%, Al 2 O 3 6.5%, Ag 2 SO 4 0.0025%, Ag 3 PO 4 0.025%, CuSO 4 0.04%, B 2 O 3 0.26%, Ca(H 2 PO 4 ) 2 2.6%, Fe 2 O 3 0.01%.

[0043] Comparative Example

[0044] Comparative Example 1

[0045] A glass, which differs from Example 1 in that Ag is used 2 SO 4 Replace CuSO with equal weight percentage 4 .

[0046] Comparative Example 2

[0047] A glass, which is different from Example 1 in that CuSO 4 Replace Ag with equal weight percentage 2 SO 4 .

[0048] Comparative Example 3

[0049] A glass, which differs from Example 1 in that Ag is used 2 SO 4 Replace Ag with equal weight percentage 3 PO 4 .

[0050] Comparative Example 4

[0051] A glass, which is different from Example 1 in that AgNO is used 3 Replace Ag with equal weight percentage 2 SO 4 and Ag 3 PO 4 .

[0052] Comparative Example 5

[0053] A glass, which differs from Example 1 in that ZnO is used in place of Ag by weight percentage. 2 SO 4 and Ag 3 PO 4 .

[0054] Data Detection

[0055] The samples prepared in the examples and comparative examples were cut into samples with a size of 10 cm×10 cm×4 cm and subjected to the following tests;

[0056] 1.1 Visible light transmittance: Test the visible light transmittance of the sample in accordance with GB / T30983-2014 Test Method for Optical Properties of Photovoltaic Glass;

[0057] 1.2 Antibacterial activity: Escherichia coli and Staphylococcus aureus were used as test bacteria. Before the test, Escherichia coli and Staphylococcus aureus were transferred to blood agar plates and incubated at 35°C for 18 hours. Two to three colonies of Escherichia coli and Staphylococcus aureus were picked from the blood agar plates and placed in broth, incubated at 35°C for 2 hours. The Escherichia coli and Staphylococcus aureus liquids were taken with a micropipette and placed on the samples, and the number of colonies on the samples after 24 hours (μg / mL) was calculated.

[0058] 1.3 Durability: The samples are placed in a salt spray test chamber for cycling, with a temperature cycle of -20 to 60°C and a humidity of 100%. After 300 days of cycling, the visible light transmittance and antibacterial properties are re-measured.

[0059] Table 1. Visible light transmittance of Examples 1-5 and Comparative Examples 1-5

[0060]

[0061] Table 2. Antibacterial properties of Examples 1-5 and Comparative Examples 1-5

[0062]

[0063] Data analysis

[0064] Comparative Example 1 and Example 1 form a single comparison. In Comparative Example 1, Ag is used 2 SO 4 Replace CuSO with equal weight percentage 4 In Comparative Example 1, the silver content is relatively high. Due to the limited solubility of silver ions in the glass melt, within this doping amount range, Al 2 O 3 and B 2 O 3 The stabilization effect on silver ions is not obvious, resulting in silver aggregation in the form of micelles. The average particle size in Comparative Example 1 increases, resulting in a significant decrease in the visible light transmittance of the vitreous body. In Comparative Example 1, point aggregation occurs, and the appearance of the vitreous body is poor. In addition, due to the lack of Cu 2+ The blockage of the diffusion channel of alkali metal ions reduces the stability of the vitreous body, making it easy for the vitreous body to mold. + The antibacterial ions such as copper ions are gradually dissolved during the mold growth process, resulting in a serious loss of antibacterial properties of the vitreous body under long-term extreme environmental erosion, and a large increase in the number of colonies. It can be concluded that the silver content in the glass melt needs to be strictly controlled. When the silver content is too high, silver is easy to form micelles in the glass melt. In Example 1, copper ions are used to replace part of the silver ions. While reducing the silver content, the antibacterial synergistic effect of copper ions and silver ions can also ensure that the vitreous body maintains relatively excellent antibacterial properties. At the same time, due to Cu 2+ It can complement the cyan color of iron ions, so that the ultra-white glass prepared in Example 1 has a good-looking light blue edge and high visible light transmittance.

[0065] Comparative Example 2 forms a single comparison with Example 1. In Comparative Example 2, CuSO 4 Replace Ag with equal weight percentage 2 SO 4 The copper content in Comparative Example 2 is relatively high. Although the visible light transmittance of Comparative Example 2 is high, its antibacterial performance is poor. During the initial antibacterial period, the number of colonies is 4 times that of Example 1. The reason is that first, Cu 2+ The antibacterial performance of Cu is weaker than that of silver ions, resulting in a weakening of the antibacterial performance; secondly, 2+ Although it can block the diffusion channels of alkali metal ions, making the vitreous body have better chemical stability, it also blocks the diffusion channels of silver ions, making it difficult for silver ions inside the vitreous body to migrate to the surface of the vitreous body, resulting in a significant weakening of the antibacterial performance.

[0066] Comparative Example 3 and Example 1 form a single comparison. In Comparative Example 3, Ag is used 2 SO4 Replace Ag with equal weight percentage 3 PO 4 The visible light transmittance of comparative example 3 is lower than that of example 1. It can be seen that the introduction of high-valent phosphorus helps to promote the number of bridging oxygens in the silicon-oxygen tetrahedral glass network, increases the density of bridging oxygen connections, and enhances the continuity of light transmission in the glass body within the visible light wavelength range, thereby improving the visible light transmittance.

[0067] Comparative Example 4 and Example 1 form a single comparison. In Comparative Example 4, AgNO 3 Replace Ag with equal weight percentage 2 SO 4 and Ag 3 PO 4 In comparative example 4, silver ions are in the form of AgNO 3 In this vitreous system, after actual testing, AgNO 3 It is easy to cause a significant decrease in the visible light transmittance of the vitreous body, which may be due to the fact that AgNO 3 The decomposition temperature of AgNO is low, and the glass melt produces many small bubbles at high temperature, which are difficult to melt. It is difficult to completely remove the small bubbles at the high temperature stage of glass melt, resulting in a decrease in the optical properties of the glass. 3 and CuSO 4 The antibacterial effect of the combination is inferior to that of Ag 2 SO 4 、Ag 3 PO 4 and CuSO 4 The reason may be that Ag 2 SO 4 The high decomposition temperature makes it easier for silver ions to migrate to the surface of the vitreous body, significantly improving the antibacterial properties.

[0068] Comparative Example 5 is compared with Example 1. In Comparative Example 5, ZnO is used in place of Ag by weight. 2 SO 4 and Ag 3 PO 4 ZnO can play a certain antibacterial role through photocatalysis, but when it is added to the glass, it occupies the Ag + vacancies, resulting in Ag + Ag forms micelles in the glass, which results in a darker color of the glass melt and a decrease in visible light transmittance. 4 The antibacterial performance of the combination is significantly lower than that of Ag 2 SO 4 、Ag 3 PO 4 and CuSO4 The combination shows that the antibacterial effect of zinc oxide through photocatalysis is not as good as that of silver ions.

[0069] Example 1-2 forms a single contrast, Ag 2 SO 4 、Ag 3 PO 4 and CuSO 4 The ratio of Ag in the vitreous body was significantly improved. + The distribution and aggregation state of the nanostructured particles affect the visible light transmittance and antibacterial properties of the vitreous body. 2 O, MgO, Al 2 O 3 , B 2 O 3 , Ca(H 2 PO 4 ) 2 The change of the content of additives such as Ag also has a significant impact on the visible light transmittance and antibacterial properties of the glass. It is necessary to adjust each additive to a suitable ratio so that the glass melt can maintain a low viscosity throughout the melting process and make Ag + Maintaining good stability reduces the possibility of aggregation into colloids, and the antibacterial ions are more likely to migrate to the vitreous surface, achieving a better antibacterial effect.

[0070] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0071] Moreover, the above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A high-performance ultra-white glass, characterized in that: It is composed of the following raw materials in weight percentage: SiO271.6~72.2%, Na2O 10.1~11.7%, MgO 7.2~8.2%, Al2O36.5~7.0%, Ag2SO40.0025~0.003%, Ag3PO40.02~0.025%, CuS O40.03~0.04%, B2O30.24~0.26%, Ca(H2PO4)21.4~2.6%, Fe2O30.008~0.01%.

2. The high-performance ultra-white glass according to claim 1, characterized in that: The weight percentage of Ag2SO4 in the high-performance ultra-white glass is 0.0025%, the weight percentage of Ag3PO4 is 0.025%, and the weight percentage of CuSO4 is 0.04%.

3. The high performance ultra-white glass according to claim 1, characterized in that: The weight percentage of Al2O3 in the high-performance ultra-white glass is 7.0%, and the weight percentage of B2O3 is 0.25%.

4. The high-performance ultra-white glass according to claim 1, characterized in that: The weight percentage of Na2O in the high-performance ultra-white glass is 10.4-10.6%, the weight percentage of Ca(H2PO4)2 is 2.0-2.6%, and the weight percentage of MgO is 7.5-8.0%.

5. The high-performance ultra-white glass according to claim 4, characterized in that: The weight percentage of Na2O in the high-performance ultra-white glass is 10.5%, the weight percentage of Ca(H2PO4)2 is 2.5%, and the weight percentage of MgO is 7.8%.

6. A method for preparing high-performance ultra-white glass according to any one of claims 1 to 5, characterized in that: The steps include: The raw materials are weighed according to weight percentage, mixed, ground, melted at high temperature, cooled and formed, and annealed to obtain high-performance ultra-white glass.